2006
DOI: 10.1186/1475-925x-5-27
|View full text |Cite
|
Sign up to set email alerts
|

The imperative for controlled mechanical stresses in unraveling cellular mechanisms of mechanotransduction

Abstract: Background: In vitro mechanotransduction studies are designed to elucidate cell behavior in response to a well-defined mechanical signal that is imparted to cultured cells, e.g. through fluid flow. Typically, flow rates are calculated based on a parallel plate flow assumption, to achieve a targeted cellular shear stress. This study evaluates the performance of specific flow/perfusion chambers in imparting the targeted stress at the cellular level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…In previous computational studies of PPFC systems, it is the shear stress that is considered to dominate the applied mechanical stimulus. A number of CFD simulations have highlighted amplifications in the target WSS along the cell membrane [21][22][23], similar to that observed in our local FSI model (figure 4a), however do not consider the potentially significant contribution of pressure acting on the cell membrane. If cellular response under fluid flow is assumed to be a strain-activated mechanism, then the local FSI model results herewith are in agreement with the experimental studies of Huesa et al [16] who predicted that the stimulation of cells in a PPFC was probably a result of a combined stimulus of pressure and WSS.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In previous computational studies of PPFC systems, it is the shear stress that is considered to dominate the applied mechanical stimulus. A number of CFD simulations have highlighted amplifications in the target WSS along the cell membrane [21][22][23], similar to that observed in our local FSI model (figure 4a), however do not consider the potentially significant contribution of pressure acting on the cell membrane. If cellular response under fluid flow is assumed to be a strain-activated mechanism, then the local FSI model results herewith are in agreement with the experimental studies of Huesa et al [16] who predicted that the stimulation of cells in a PPFC was probably a result of a combined stimulus of pressure and WSS.…”
Section: Discussionsupporting
confidence: 74%
“…To date, the main design criteria associated with PPFCs has been to establish a suitable homogeneous wall shear stress (WSS) profile in the region where cultured cells are located [20]. Computational fluid dynamics (CFD) approaches have been applied to predict the mechanical stresses acting on a single-cell monolayer [21] and multi-cell monolayer arrays [22,23] under laminar flow in PPFC systems. Such studies have predicted that there is significant amplification of shear stress (approx.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, due to the high resolution of our local sub-scaffold FSI model, it was shown that the WSS was amplified significantly at the cell level when compared to the predicted WSS from the global model, with certain cases exhibiting a five-fold increase. Interestingly, similar cell level amplification effects of WSS have been observed for 2D cell perfusion systems (Anderson et al 2006;Vaughan et al 2013). However, in 2D cell perfusion systems, the WSS magnitudes to stimulate a biochemical response of cells in osteogenic and chondrogenic differentiation were much higher than the levels of WSS in our study.…”
Section: Discussionsupporting
confidence: 69%